Influence of cataract on image quality and macular thickness measured using spectral domain optical coherence tomography: a prospective cohort study - Lathika, Vasu Kamaladevi; Minu, Susan Prakash; Charles, K. Skariah (International Journal of Advances in Medicine, 2017)
Background: Optical coherence tomography (OCT) is one of the most useful imaging techniques in the management of retinal diseases affecting the macula. Factors affecting the image quality of OCT may affect the macular thickness and hence treatment of retinal pathologies. This study was aimed to evaluate the influence of cataract on macular scans using spectral domain OCT. Methods: The prospective study was done in 36 patients with cataract. Cataract was graded as cortical, nuclear or posterior cataracts. All patients underwent small incision cataract surgery. Pre and post-operative imaging of the macula (4 weeks after surgery) using spectral domain OCT. The signal strength and central macular thickness (CMT) measurements were made before and after the surgery and analysed statistically. Results: The majority (66.7%) of patients had posterior cataracts. A statistically significant improvement in OCT image quality (as assessed by signal strength) was noted post operatively. This was maximum for posterior cataracts (2.9), followed by cortical cataract (1.6), while nuclear cataracts had the least increase in signal strength (1.3). The difference in signal strength gain between posterior and nuclear cataracts was found to be statistically significant (p = 0.05). The increase in CMT was clinically significant only in 8.2% of the study population. No patient with nuclear cataract had a clinically significant increase in CMT following surgery. Conclusions: Cataract can influence OCT image quality as well as central macular thickness measurements. Both were found to be affected maximally by posterior cataracts, followed by cortical, while nuclear cataracts had the least influence.